THE EFFECT OF SELF-EFFICACY MEDIATION TO THE INFLUENCE BETWEEN TEACHER EXPERIENCE AND TEACHER TRAINING TOWARDS TECHNOLOGICAL PEDAGOGY AND CONTENT KNOWLEDGE - Kodri, Kodri; Budiwati, Neti; Adirestuty, Fitranty (The International Journal of Business Review (The Jobs Review), 2019)
This research was inspired by the rapid development of information and communication technology. It obligates teachers to apply technology and information in learning for enriching their professionalism. This research aims to determine the significance of the effect on teacher experience, training, and self-efficacy on TPACK, as well as determining the significance of teacher experience and training on self-efficacy. The used method in this research was descriptive method with data collection techniques through distributing questionnaires to economics teachers. Path analysis technique is used to analyze the data. Based on the results of the analysis, it was found that teacher experience, training, and self-efficacy had a significant positive effect on TPACK. Teacher experience and training have a significant positive effect on self-efficacy. Yet, self-efficacy is not able to mediate the effect of teacher experience on TPACK, and the effect of training on TPACK.